Crime is in the air: the contemporaneous relationship between air pollution and crime - Bondy, Malvina (2020)
Many empirical studies have examined the various determinants of crime. However, the link between crime and air pollution has been largely overlooked. In this paper we study whether exposure to ambient air pollution affects crime using daily administrative data for London in 2004-05. For identification, we estimate models with ward fixed effects and implement two instrumental variable strategies, using atmospheric inversions and wind direction as exogenous shocks to local pollution. We find that air pollution has a positive and statistically significant impact on overall crime and on several major crime categories, including those with economic motives. Importantly, the effect also occurs at pollution levels which are well below current regulatory standards and appears to be unevenly distributed across income groups. Our results suggest that reducing air pollution in urban areas may be an effective measure to reduce crime and that air pollution forecasts can be used to improve predictive policing